2014 IEEE Symposium on Evolving and Autonomous Learning Systems (EALS) 2014
DOI: 10.1109/eals.2014.7009510
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic generation via parameter tuning for online bin packing

Abstract: Abstract-Online bin packing requires immediate decisions to be made for placing an incoming item one at a time into bins of fixed capacity without causing any overflow. The goal is to maximise the average bin fullness after placement of a long stream of items. A recent work describes an approach for solving this problem based on a 'policy matrix' representation in which each decision option is independently given a value and the highest value option is selected. A policy matrix can also be viewed as a heuristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A recent study byÖzcan and Parkes found that good (optimal) policies could actually be 'spiky' and complex [11,13]. Recent research in bin packing has tended to focus on metaheuristic strategies capable of automatically devising policies which are more complex than FF or BF and better suited to solving the problem [11,14,13].…”
Section: Previous Approaches For Online One-dimensional Bin Packingmentioning
confidence: 99%
“…A recent study byÖzcan and Parkes found that good (optimal) policies could actually be 'spiky' and complex [11,13]. Recent research in bin packing has tended to focus on metaheuristic strategies capable of automatically devising policies which are more complex than FF or BF and better suited to solving the problem [11,14,13].…”
Section: Previous Approaches For Online One-dimensional Bin Packingmentioning
confidence: 99%
“…Hence, online bin packing forms a good playground for testing the proposed approach. The first results (reported in [24] and later in [4] and [36]) indicates that the GA approach finds high quality policies for the specific packing problems that perform significantly better than the generic 'human designed' heuristics, such as, first fit and best fit [27,10]. In this paper, we show that by modifying mutation probabilities using tensor analysis, the performance of this framework can be improved significantly (when compared to the results achieved for our implementation of the GA approach in [24] as well as standard heuristics) on almost all instances.…”
Section: Introductionmentioning
confidence: 99%
“…In [5] an Apprenticeship Learning approach was proposed where an agent observes and learns the actions of high quality policy matrices during packing and generalizes its knowledge to unseen instances of various sizes exhibiting high performance particularly for larger instances. In [36], policy matrices are seen as heuristics with many parameters and are approached from a parameter tuning perspective. The Irace package was used to tune policies during training.…”
Section: Policy Matrix Representationmentioning
confidence: 99%
“…Yarimcam et al (2014) showed that applying a parameter tuning approach does not match the performance of GA in the overall. Asta et al (2013b) showed that k-means clustering can be used to generalise the behaviour of GA for solving a given online bin packing problem.…”
Section: Introductionmentioning
confidence: 99%
“…The authors formulated the whole process as a special type of parameter tuning (Smit and Eiben, 2009;Yarimcam et al, 2014) in which the number of parameters is much larger than usually considered.…”
Section: Introductionmentioning
confidence: 99%